PENGARUH PERCEIVED RISK DAN CUSTOMER SATISFACTION TERHADAP PURCHASE INTENTION DAN INTENTION TO REVISIT PADA GRAMEDIA ONLINE SURABAYA - JULIANTO, STEVEN (Kajian Ilmiah Mahasiswa Manajemen, 2012)
Along with the development of the internet rapidly increasing, thus causing Retail Companies have to follow it. One of the Retail Companies that follow the development of the Internet a Gramedia Book Store, which makes online sites, namely Gramedia Online.com. Along with that, the advent of these online sites will also lead to consumer perceptions of the risks of online site so that these risks will bean effect on consumer purchase intention and intention to visit again at the online site, and besides that, it is necessary also to pay attention to customer satisfaction. The purpose of this study was to determine the effect of Perceived Risk and Customer Satisfaction against Purchase Intention and Intention to Revisit the Gramedia Online Surabaya. Techniques used in the study sampling this is a non-probability sampling. Mean while, the analysis technique used is to use them method of Structural Equation Modeling (SEM) with LISREL 8.70 program. The results showed that there were negative effects of Perceived Risk on Purchase Intention and Intention to Revisit. As for Customer Satisfaction positive effect on Purchase Intention and Intention to Revisit.